2019
DOI: 10.3762/bxiv.2019.155.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preparation of glyco-gold nanoparticles carrying synthetic mycobacterial hexaarabinofuranoside and their evaluation in vivo

Abstract: Some bacterial glycans are specific markers for detection and serological identification of microorganisms and are widely used as antigenic components of vaccines. The use of gold nanoparticles as carriers for glyco-epitopes is becoming an important alternative to the traditional conjugation with proteins and synthetic polymers. In this study, we aimed at preparation and evaluation in vivo of glyco-gold nanoparticles (glyco-GNPs) bearing the terminal branched hexaarabinofuranoside fragment (Ara6) of arabinan d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 92 publications
(140 reference statements)
0
2
0
Order By: Relevance
“…For immunoassay of mycobacteria, GNPs were conjugated to the penta-and hexasaccharide fragments of mycobacterial lipoarabinomannan by using aglycon spacers of various lengths [130]. Rabbit polyclonal antibodies to these conjugates were developed.…”
Section: Gold Nanoparticles In the Preparation Of Antibacterial Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…For immunoassay of mycobacteria, GNPs were conjugated to the penta-and hexasaccharide fragments of mycobacterial lipoarabinomannan by using aglycon spacers of various lengths [130]. Rabbit polyclonal antibodies to these conjugates were developed.…”
Section: Gold Nanoparticles In the Preparation Of Antibacterial Vaccinesmentioning
confidence: 99%
“…Subsequently, it was shown that vaccination of pregnant mice with gold glyconanoparticles carrying L. monocytogenes peptides protects Figure 4. Schematic illustration of modulation of antibacterial immunity with bacterial-membrane-coated nanoparticles [130].…”
Section: Gold Nanoparticles In the Preparation Of Antibacterial Vaccinesmentioning
confidence: 99%